Manfaat Pengelolaan TPS 3R Bambu Raya terhadap Pemberdayaan Sosial, Ekonomi Lokal, dan Lingkungan Berkelanjutan - Muhammad Doddy Mauluddin; Novrianus Kofi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Waste management in densely populated areas poses a serious challenge that affects public health and environmental quality. This study aims to examine the impact of the Reduce, Reuse, Recycle Waste Management Facility (TPS 3R) Bambu Raya on social empowerment, local economic growth, and sustainable environmental management in Warungbambu Village, East Karawang District. The research employed a qualitative approach using phenomenological methods through participatory observation, in-depth interviews, and documentation over a three-month period. The findings indicate that the presence of TPS 3R Bambu Raya has significantly increased community participation, fostered the formation of environmentally aware groups, and created business opportunities such as compost production and recycled crafts. Moreover, TPS 3R has reduced the amount of unmanaged waste, improved sanitation, and mitigated environmental pollution. SWOT analysis reveals that enhancing education, improving technology, and expanding collaborative networks are key strategies for sustaining the program. Overall, the management of TPS 3R Bambu Raya serves as an integrative model for inclusive and sustainable community-based development.